The Association of Surgical Timing and Injury Severity With Systemic Complications in Severely Injured Patients With Pelvic Ring Injuries. Issue 4 (April 2021) - Rojas, David G.; Coleman, Julia R.; Moore, Ernest E.; Dean, Chase S.; Parry, Joshua A.; Elrick, Bryant P.; Ryan, Weston K.; Nadeau, Jason T.; Maher, Michael; Hwang, Jihyo; Byun, Seongeun; Mauffrey, Cyril P.
Abstract : Objectives: To evaluate the relationship between timing of definitive fixation, injury severity, and the development of systemic complications in severely injured patients with pelvic ring injuries. Design: Retrospective review. Settings: Level 1 trauma center. Patients: One hundred eighteen severely injured [Injury Severity Score (ISS) ≥ 16] adult patients with pelvic ring injuries undergoing definitive fixation, excluding patients treated with external fixation for hemodynamic instability. Intervention: Early fixation (⩽36 hours) in 37 patients and delayed fixation (>36 hours) in 81 patients. Main Outcome Measurements: Systemic complications (acute respiratory distress syndrome, pulmonary embolism, deep venous thrombosis, sepsis, multi-organ failure, and death). Results: The delayed fixation group had a higher ISS and had more patients with chest injuries. There was no detectable difference in the number of patients with systemic complications between early versus delayed fixation groups [8 (22%) vs. 29 (35%), P = 0.1]. The only difference detected in specific complications was a higher incidence of pneumonia with delayed fixation [16 (20%) vs. 0 (0%), P = 0.004] with 11 of the 16 cases being associated with chest injury. Univariate analysis showed an association between complication and time to fixation, ISS, Glasgow Coma Scale, pH, base excess, and injuries to the head, chest, and abdomen. On multivariate analysis, only ISS remained significantly associated with the development of complications [Odds ratio 2.6 per 10 point increase, 95% confidence interval (CI), 1.4–4.4]. Conclusions: These data suggest that the severity of injury is most highly associated with systemic complications after definitive fixation of pelvic ring injuries. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.